Performance and design study of optimized LNG Mixed Fluid Cascade processes. (15th December 2019) - Brodal, Eivind; Jackson, Steve; Eiksund, Oddmar
Abstract: Mixed Fluid Cascade (MFC) processes are often claimed to be one of the most efficient methods to liquefy natural gas. Their performance depends on both operating conditions such as ambient temperature, and system design parameters such as exchanger sizes. The performance of the standard MFC process can be further improved by modifying the design with additional equipment, such as liquid refrigerant expanders or additional pressure levels in the refrigerant cycles. This article presents a performance study of several modified MFC processes. Results are obtained using multivariable optimization algorithms in MATLAB and a process model developed in HYSYS. Constraints related to minimum internal temperature approach are used to model the main heat exchangers. The results illustrate the impact of ambient temperature on performance, and that modifications with either two-stage pre-cooling systems or liquid expanders reduce the power consumption by 3.0%–4.5%, translating into a 15%–30% reduction in the combined UA values of the main heat exchangers. Highlights: Assessment of ambient temperature impact on MFC performance parameters. Modelling MFC refrigerant cycles modified with liquid expanders. Modelling of MFC processes modified with two-stage pre-cooling systems. Optimizing approach based on heat exchanger outlet temperature differences. Results showing why exchangers should be modelled with internal temperature pinches.